Vascular endothelial cadherin controls VEGFR-2 internalization and signaling from intracellular compartments - Lampugnani, Maria Grazia; Orsenigo, Fabrizio; Gagliani, Maria Cristina; Tacchetti, Carlo; Dejana, Elisabetta (The Journal of cell biology, 2006)
Receptor endocytosis is a fundamental step in controlling the magnitude, duration, and nature of cell signaling events. Confluent endothelial cells are contact inhibited in their growth and respond poorly to the proliferative signals of vascular endothelial growth factor (VEGF). In a previous study, we found that the association of vascular endothelial cadherin (VEC) with VEGF receptor (VEGFR) type 2 contributes to density-dependent growth inhibition (Lampugnani, G.M., A. Zanetti, M. Corada, T. Takahashi, G. Balconi, F. Breviario, F. Orsenigo, A. Cattelino, R. Kemler, T.O. Daniel, and E. Dejana. 2003. J. Cell Biol. 161:793-804). In the present study, we describe the mechanism through which VEC reduces VEGFR-2 signaling. We found that VEGF induces the clathrin-dependent internalization of VEGFR-2. When VEC is absent or not engaged at junctions, VEGFR-2 is internalized more rapidly and remains in endosomal compartments for a longer time. Internalization does not terminate its signaling; instead, the internalized receptor is phosphorylated, codistributes with active phospholipase C-gamma, and activates p44/42 mitogen-activated protein kinase phosphorylation and cell proliferation. Inhibition of VEGFR-2 internalization reestablishes the contact inhibition of cell growth, whereas silencing the junction-associated density-enhanced phosphatase-1/CD148 phosphatase restores VEGFR-2 internalization and signaling. Thus, VEC limits cell proliferation by retaining VEGFR-2 at the membrane and preventing its internalization into signaling compartments.